Comparison of slow and fast pyrolysis for converting biomass into fuel. (August 2018) - Al Arni, Saleh
Abstract: In this work, the conversion of sugarcane bagasse into fuel was studied as a low cost source material. The conversion was carried out experimentally in a batch pyrolysis reactor. Two pyrolysis methods were compared; namely, fast pyrolysis and slow or conventional pyrolysis. This comparison was based on the thermal decomposition of biomass into fuel and on the product yields. Since the yields are affected by the type of pyrolysis and the operating temperature of the reactor, the comparisons have been conducted at three fixed temperature values of 753, 853 and 953 K. The results revealed that the conventional pyrolysis produce more syngas yield with the increases of temperature. In the case of fast pyrolysis, it was observed that losses and solid yield increase with temperature increase. Moreover, it was found that the highest losses in both cases are less than 15% and that it was higher in conventional pyrolysis. Gases released during the thermal decomposition of biomass were identified as H2, CO, CO2, CH4 and some light molecular weight of hydrocarbons, such as C2 H4 and C2 H6 . The low temperature was favored for the production of methane other than hydrogen for both processes, while high temperature was favored for the production of hydrogen. The produced H2 can be used in typical fuel cells. Graphical abstract: Highlights: A comparison between two-type pyrolyses for syngas from bagasse is presented. Fast pyrolysis at high temperature favors the production of hydrogen. Slow pyrolysis favors syngas production while fast pyrolysis favors char production. Maximum value obtained of H2 is 45 vol% at 953 K, while for CH4 is 30 vol% at 853 K.